Studies of Photoinduced Molecular Dynamics Using a Fast Imaging Sensor - Slater, Craig S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The work presented in this thesis involves a number of sophisticated experiments highlighting novel applications of the Pixel Imaging Mass Spectrometry (PImMS) camera in the field of photoinduced molecular dynamics. This approach represents the union of a new enabling technology (a multiple memory register, CMOS-based pixel detector) with several modern chemical physics approaches and represents a significant leap forward in capabilities. Applications demonstrated include three-dimensional imaging of photofragment Newton spheres, simultaneous electron-ion detection using a single sensor, and ion-ion velocity correlation measurements that open the door to novel covariance imaging experiments. When combined with Coulomb explosion imaging, such an approach is demonstrated to allow the measurement of molecular structure and motion on a femtosecond timescale. This is illustrated through the controlled photoexcitation of torsional motion in biphenyl molecules and the subsequent real-time measurement of the torsional angle.
Introduction and Motivation -- Experimental Techniques and Methods of Data Analysis -- Three-Dimensional Velocity-Map Imaging -- Pulsed-Field Electron-Ion Imaging -- Principles of Coulomb Explosion Imaging -- Investigations of Coulomb Explosion Dynamics -- Time-resolved Studies of Induced Torsional Motion.
Keywords: Spectrum analysis; Physical chemistry; Atomic structure .; Molecular structure .; Spectroscopy; Physical Chemistry; Atomic and Molecular Structure and Properties